Emerging Carbapenem Resistance Among Nosocomial Isolates of Klebsiella Pneumoniae in South India - R. MOHAMUDHA PARVEEN; B.N.HARISH; S.C.PARIJA (International Journal of Pharma and Bio Sciences, 2010)
Multidrug resistant Klebsiella pneumoniae are an increasingly difficult problem in Indian hospitals. Carbapenems have been the grounding of drug treatment for serious infections caused by these pathogens. Resistance to carbapenems has been unknown until now. The purpose of this study was to examine the prevalence of carbapenem resistance among K. pneumoniae in a tertiary care hospital. A total of 134 clinical isolates of K. pneumoniae were studied. Minimum inhibitory concentration for meropenem, colistin in resistant isolates, Metallo-beta-lactamases detection and modified Hodge’s test for carbapenemase detection were done. About 43.6% percent isolates were resistant to meropenem, 32% to imipenem, 20.3% to ertapenem and 60% were resistant to colistin. None of them were Metallo-beta-lactamases producers. Six isolates showed Modified Hodge’s test positive with dissimilar clonal types. This is the first report of Klebsiella Pneumoniae Carbapenemase (KPC) producing K.pneumoniae from India.